Correlation of matrix metalloproteinase-9 expression with morphometric analysis of mucosal vasculature in oral squamous cell carcinoma, oral epithelial dysplasia, and normal oral mucosa - Jose, Deepa; Mane, Deepa Rajesh (International Journal of Health Sciences, 2018)
Objective: Oral squamous cell carcinoma (OSCC) invades and metastasizes, by degrading the extracellular matrix (ECM) and is associated with poor prognosis. Matrix-metalloproteinase (MMP-9) can initiate ECM degradation and angiogenesis which brings a significant change in tumor microenvironment favoring tumor progression. A major thrust has been laid on understanding this key enzyme as it has significant implications for cancer therapy. Comprehending the association of vasculature with MMP-9 expression in precancerous lesions oral epithelial dysplasia (OED) and OSCC is essential since the data regarding the same are fewer. The aim is to evaluate and correlate MMP-9 expression with morphometric analysis of mucosal vasculature in the normal oral mucosa (NOM), OED, and OSCC. Methods: A total of 60 histologically diagnosed cases of OED (n = 30); OSCC (n = 30); along with 10 NOM (n = 10) as control were included. Immunohistochemical staining of MMP-9 and vascular morphometric analysis was performed for all the cases. Results were analyzed using the Chi-square test, Fischer exact test, and Spearman correlation test. Results: A statistically significant difference in MMP-9 was noted among the groups with P = 0.011* (epithelium); P = 0.001* (stroma) by the highest value in OSCC group. Morphometry also revealed a progressive increase from NOM to OED to OSCC. Spearman’s correlation of MMP-9 with vascular parameters illustrated a positive relation of MMP-9 with mean vascular density (MVD) and mean vascular area percentage (MVAP). Conclusion: Positive correlation of MMP-9 with MVD and MVAP demonstrates this markers effect on angiogenesis. Henceforth, MMP-9 can be embattled as a potential therapeutic target in combating tumor progression.